Mitigation of Fire Risk Using HIRARC Method in a Flexible Plastic Printing Company - Rabbani Arieza Satya Yoga; Mokh. Suef; Indung Sudarso (Institut Teknologi Sepuluh Nopember, 2019)
Fires are incidents and must be considered in all types of industrial production activities. In the last 2 years there were some incidence of fires on PT. XYZ, plastic printing company, 6 cases of small fires and 3 cases of large fires. The fire incident caused big losses, machine stopfor a long time and paId the employees fee who kept coming to work when the machine was being repaired. Main objective of this research is how to prevent fires and its causes and how to mitigate the fireusing the HIRARC method. The researchwas carried out in three main stages: The hazard identification stage, The risk assessment stage, and The risk control.The risk control was carried out based on 5 hierarchical risk control analysisto minimize the high risk of fire that can disrupt production activities in the company. The result of focusgroup discussion, the main cause of fire incident is the static electricity. Due to routine maintenance of the machines that currently have not been maximized, a maintenance strategy have been developed and inserted into the company risk management system